2022
DOI: 10.1088/1741-4326/ac65a0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of impurity ions on the coupling between zonal flow and local turbulent transport in HL-2A plasmas

Abstract: The effect of impurity ions on the coupling between geodesic acoustic mode (GAM) zonal flows and local turbulent transport has been studied using a Langmuir probe array in HL-2A ohmically-heated deuterium plasmas. The experimental results illustrate that both frequency and amplitude level of the GAM zonal flow significantly reduce with the increase of carbon ions concentration, which is qualitatively consistent with the theoretical prediction [B. Xie et al. Plasma Phys. Controlled Fusion 60 025015 (2018)], mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…, σ k is the averaged wavenumber broadening [46]. It is found that both L cθ and L cr increase significantly in the positive bias case, but change little in the negative bias case, revealing that the spatial dimensions of the turbulent eddies are enlarged in the positive bias case.…”
Section: Effects Of Different Bias Voltages On Spatial Structures Of ...mentioning
confidence: 93%
“…, σ k is the averaged wavenumber broadening [46]. It is found that both L cθ and L cr increase significantly in the positive bias case, but change little in the negative bias case, revealing that the spatial dimensions of the turbulent eddies are enlarged in the positive bias case.…”
Section: Effects Of Different Bias Voltages On Spatial Structures Of ...mentioning
confidence: 93%
“…Recently, studies of the role played by impurity ions on turbulence and plasma confinement have been extensively carried out, such as, neon seeding in DIII-D [10], nitrogen seeding in AUG [11], helium seeding in T-10 [12], boron injection in EAST [13] and LHD [14], and carbon and tungsten injection in HL-2A [15,16]. A study that has attracted great attention is the one on tungsten, mainly because tungsten has been chosen as the plasma-facing material in ITER due to its high erosion resistance and good thermal conductivity [17].…”
Section: Introductionmentioning
confidence: 99%